2020
DOI: 10.1111/nph.16777
|View full text |Cite
|
Sign up to set email alerts
|

TRICHOME AND ARTEMISININ REGULATOR 2 positively regulates trichome development and artemisinin biosynthesis in Artemisia annua

Abstract: Glandular secretory trichomes (GSTs) are regarded as biofactories for synthesizing, storing, and secreting artemisinin. It is necessary to figure out the initiation and development regulatory mechanism of GSTs to cultivate high-yielding Artemisia annua. Here, we identified an MYB transcription factor, AaTAR2, from bioinformatics analysis of the A. annua genome database and Arabidopsis trichome development-related genes. AaTAR2 is mainly expressed in young leaves and located in the nucleus. Repression and overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 46 publications
(56 reference statements)
0
36
0
Order By: Relevance
“…AaORA down-regulation by hairpin-mediated RNAi decreased dihydroartemisinic acid as well as artemisinin. Zhou et al (2020) identified an MYB transcription factor, AaTAR2 which acts as a positive regulator of glandular trichome initiation and development, and its over-expression resulted in increased artemisinin content. Recently, Qin et al (2021) isolated and characterized another glandular trichome specific transcription factor AaMYB17 in A. annua.…”
Section: Transgenic Approachesmentioning
confidence: 99%
“…AaORA down-regulation by hairpin-mediated RNAi decreased dihydroartemisinic acid as well as artemisinin. Zhou et al (2020) identified an MYB transcription factor, AaTAR2 which acts as a positive regulator of glandular trichome initiation and development, and its over-expression resulted in increased artemisinin content. Recently, Qin et al (2021) isolated and characterized another glandular trichome specific transcription factor AaMYB17 in A. annua.…”
Section: Transgenic Approachesmentioning
confidence: 99%
“…S12). Through a gene regulatory network, 21 GA‐responsive TFs were selected (correlation threshold > 300) for future study and considered potential regulators in trichome development and artemisinin biosynthesis (Dataset S3) (Zhou et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The Artemisia annua cultivar used in this study was ‘Huhao 1’ (Zhou et al ., 2020). Young leaves of Artemisia annua were collected for phytohormone quantification and transcriptome analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the R2R3-MYB genes have been shown to play regulatory roles in flavonoid biosynthesis in A. annua . Recently, the MYB family transcription factor AaTAR2 from A. annua was reported to synergistically regulate both artemisinin and flavonoids 29 ; however, the mechanism of the regulation of flavonoid biosynthesis was not found. In plants, flavonoid biosynthesis is tightly regulated by MBW complexes that interact with late biosynthetic genes.…”
Section: Introductionmentioning
confidence: 99%